2020
DOI: 10.1111/jph.12969
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical responses of tomato plants to white mold affected by manganese phosphite

Abstract: Considering the potential of white mold, caused by the fungus Sclerotinia sclerotiorum, to reduce tomato production, this study aimed to determinate the effect of manganese (Mn) phosphite on the resistance of tomato plants to this disease by assessing the photosynthetic performance (gas exchange and chlorophyll a fluorescence), the activities of defence enzymes and those related to the antioxidant metabolism as well as the concentrations of photosynthetic pigments, malondialdehyde (MDA), hydrogen peroxide (H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…In a previous study, upregulation of cat in dun ower was found to be able toimprove resistance to S. sclerotiorum (Na et al 2018). In another study, the downregulation of pod and apx in tomato by the treatment of manganese phosphit could reduce the disease severity caused by S. sclerotiorum (Chaves et al 2021). The downregulation of sod expression was previously found to improve soybean resistance to S. sclerotiorum after sprayed with calcium (Arfaoui et al 2018).…”
Section: Discussionmentioning
confidence: 91%
“…In a previous study, upregulation of cat in dun ower was found to be able toimprove resistance to S. sclerotiorum (Na et al 2018). In another study, the downregulation of pod and apx in tomato by the treatment of manganese phosphit could reduce the disease severity caused by S. sclerotiorum (Chaves et al 2021). The downregulation of sod expression was previously found to improve soybean resistance to S. sclerotiorum after sprayed with calcium (Arfaoui et al 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, the effect of the IR stimulus in reducing ASR symptoms was strikingly similar to that in studies reporting the use of ASM to establish SAR in some cash crops (Lyon, 2007). In soybean, the spray of ASM reduced soybean severity (Cruz et al, 2013) (12,13,14,15,16,17,18,19,20,21,22,23 and 24,respectively,to PAL1.1,PAL1.3,PAL2.1,PAL3. and suppression of spore germination (Chaves et al, 2020;Fagundes-Nacarath et al, 2018;Mohammad et al, 2021). Interestingly, the IR stimulus used in the present study had no effect on inhibiting urediniospore germination in vitro, highlighting its prominent role in triggering soybean resistance against P. pachyrhizi infection.…”
Section: Discussionmentioning
confidence: 99%
“…In soybean, the spray of ASM reduced soybean severity (Cruz et al, 2013). The phosphites can inhibit in vitro different physiological events in plant pathogens (e.g., Colletotrichum lindemuthianum , Sclerotinia sclerotiorum and different species of oomycetes) that will result in less mycelial growth and suppression of spore germination (Chaves et al, 2020; Fagundes‐Nacarath et al, 2018; Mohammad et al, 2021). Interestingly, the IR stimulus used in the present study had no effect on inhibiting urediniospore germination in vitro, highlighting its prominent role in triggering soybean resistance against P .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations